Coupled-inductor-based bidirectional Z-source breaker for DC system protection - Marwaha, Mridul (2021)
A coupled-inductor-based bidirectional Z-source breaker topology is introduced in this paper, which has the ability to detect and isolate the faulty section of the dc power system. Compared to existing topologies, the proposed topology utilizes a lower number of components and the coupled inductors reduce the footprint of the breaker. Analytical design equations are derived for the sizing of inductors and capacitor. Fault condition is analyzed to compute the essential criteria for the breaker to operate. Operation under step load and fault conditions are validated by simulation in both SPICE and MATLAB/Simulink environment.